The Effect of Brand Experience, Brand Personality and Brand Trust on Brand Loyalty - Howardi Visza Adha; Wiry Utami (Journal of Business and Management Review, 2021)
This study conducted to determine the effect of brand experience, brand personality and brand trust on brand loyalty. This study is an explanatory research. The method used in this study is a quantitative method using survey methods. The total sample in this study was 150 respondents with the technique of taking with the method of purposive sampling. Primary data in this research is obtained from questionnaires distributed to respondents, while secondary data is data related to the object of research presented by other parties. Data analysis techniques in this study using simple regression analysis. The result of the research shows that: (1) brand experience has positive effect on brand personality, (2) brand experience has positive effect on brand trust, (3) brand personality positive effect on brand loyalty, (4) Brand trust has positive effect on brand loyalty (5) Brand experience has positive effect on brand loyalty.